Physical property modifications with transition metal doping in nanostructured Zn1-xNixO (x = 0.03, 0.05); synthesized by chemical co-precipitation technique. Issue 1 (1st September 2022) - Ghosh, Soumyadev; Pramanik, Subhamay; Kuiri, Probodh K.; Samanta, Saikat; Sen, Rupam; Neogi, Swarup Kumar
Abstract : Present work demonstrate the structural and optical property study of Zn1-x Nix O (x= 0.03, 0.05) nanoparticles (NPs). These samples have been prepared by simple chemical co-precipitation method. Finally these samples are annealed at 500°C for 3 hours. Structural characterization has been performed by doing X-Ray diffraction (XRD) at room temperature. The XRD patterns confirm the hexagonal wurzite structure for these samples. We have estimated the lattice parameters ( a & c ) and determine the c/a ratio of respective samples after structural analysis. Morphology of these nanoparticles has been investigated by performing SEM. In addition UV-visible and Photoluminescence (PL) study has been performed. PL emission spectra show a broad UV emission peak. Doping at the Zn-site by Ni ions could induce inter-band levels within the band gap. Transition between those levels may responsible for broadening of the UV peak. In addition defect mediated visible emission has also been observed in the PL study. Further to investigate the effect of doping on microstructure, Raman spectra of Zn1-x Nix O samples are taken. Wurzite ZnO belongs to space group: C4 6v and consequently six first order phonon modes are expected to appear in the Raman spectra. Raman scattering has been analysed according to the existing literature and details of analysis are presented in this work.